Caracterização química preliminar e atividades biológicas de extratos e frações da macroalga marinha parda Lobophora variegata (J. V. Lamouroux) Womersley Ex E. C. Oliveira (Ochrophyta: Phaeophyceae) - Sousa, Karolina Costa de (2023)
Brown marine macroalgae are important sources of bioactive compounds with numerous biological activities. The general objective of this work was to preliminarily characterize the main classes of compounds present in the brown seaweed Lobophora variegata (Ochrophyta: Phaeophyceae), collected at Praia de Paracuru-Ceará, evaluate its biotechnological potential and select samples capable of being incorporated into carrageenan matrices for the preparation of edible films. The methodology used included washing, lyophilization and grinding of algal biomass, which was extracted in ethanol (EtOH), hexane (Hx), dichloromethane (DCM), ethyl acetate (AcOEt) and methanol (MeOH). The highest yield (11.95%) was in the EtOH extract. The EtOH extract was subjected to column chromatography (CC), obtaining the fractions (Hx, DCM, AcOEt, EtOH, MeOH, MeOH-n-butanol, n-butanol and water). The chromatographic profiles of the extracts and fractions indicated the presence of phenols with several compounds with Rf = 0.50 mm and polar characteristics. The quantification of total phenolic compounds (TPC) and flavonoids (TF) contents was highest in EtOH (76.013 mg EAG/g) and EtOAc (105.310 mg EQ/g) extracts. The determination of in vitro antioxidant activity: DPPH radical scavenging capacity, ferrous ion chelation power (FIC), ferric ion reducing power (FRAP) and β-carotene bleaching inhibitory activity (BCB) was performed by colorimetric methods. EtOH extract and fraction showed the best antioxidant activities (DPPH, FRAP and BCB). In addition, the antibiotic activity was also determined by the microdilution method in plates, at different concentrations, by the minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and minimum inhibitory concentration to kill 50% (IC50) of the Escherichia coli and Staphylococcus aureus strains. Non-polar compounds from the Hx extract (7.81 µg/mL) and fraction (125 µg/mL) showed potential against E. coli strains. Hx and EtOH extracts and fractions showed no activity against Aspergillus niger at different concentrations. These samples tested at a concentration of 100 µg/mL did not show phytotoxic activity against Cucumis sativus cucumber seeds. The determinations of relative percentage of germination (RSG, %), relative percentage of root growth (RRG, %) and germination index (GI, %) indicated that the samples were potentiators of germination and growth of cucumber roots. The cytotoxic activity of the Hx and EtOH extracts and fractions, against Artemia sp. nauplii, at concentrations from 12.5 to 100 μg/mL, revealed cytotoxicity of the Hx extract after 48 h of exposure, with a mortality of 72.5% of individuals. The quality of the films, incorporated with 1, 2 and 4 mg of the Hx extract and fraction, was evaluated in terms of water vapor permeability (WVP), water solubility (S) and color. The smallest WVP (0.203 g/m2 day atm) was registered in the Hx fraction. The Hx extract and fraction were soluble in water. For color coordinates (L*, a* and b*), the Hx extract and fraction showed color in the white/red/yellow range. Thus, extracts and fractions of the ochrophyte L. variegata and the compounds present in them have compounds endowed with the biological activities registered here.